2021
DOI: 10.1186/s12913-021-07255-w
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of compassionate use of medicines

Abstract: Background Compassionate use programs (CUP) for medicines respond to the ethical imperative of providing access to medicines before marketing approval to patients not recruited in trials. The economic impact of clinical trials has previously been investigated. No evidence on the net economic benefit of CUP exists. This research aims to address this information gap by estimating the economic consequences of 11 CUP in Italy conducted between March 2015 and December 2020 from the perspective of pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 41 publications
1
4
0
7
Order By: Relevance
“…In many cases, compassionate use represents an early access tool to bridge the gap between approval and reimbursement timelines. Jommi et al in 2021 estimated that avoided drug costs reported in compassionate use studies measuring only drug costs ranged from €1,746 to €49,301 per patient 21. Our analysis confirms that the guarantee of the free supply of drugs by the pharmaceutical company for compassionate use represents an important economic opportunity.…”
Section: Discussionsupporting
confidence: 77%
“…In many cases, compassionate use represents an early access tool to bridge the gap between approval and reimbursement timelines. Jommi et al in 2021 estimated that avoided drug costs reported in compassionate use studies measuring only drug costs ranged from €1,746 to €49,301 per patient 21. Our analysis confirms that the guarantee of the free supply of drugs by the pharmaceutical company for compassionate use represents an important economic opportunity.…”
Section: Discussionsupporting
confidence: 77%
“…These additional costs may affect CU activity, especially in countries where health care costs are paid out of pocket. 47 Overall, there is a need for the active involvement and collaboration of several stakeholders, including regulators, industry, physicians, and patients, for the CU access process to better address patients’ needs and to specifically support countries in building up their CU access capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the provision of therapeutic products is generally free of charge in CU, ancillary costs may have to be borne by the patient, health care professionals, or third-party payers, depending on the local circumstances. These additional costs may affect CU activity, especially in countries where health care costs are paid out of pocket . Overall, there is a need for the active involvement and collaboration of several stakeholders, including regulators, industry, physicians, and patients, for the CU access process to better address patients’ needs and to specifically support countries in building up their CU access capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A questi vantaggi, si associano i benefici dei programmi di uso compassionevole (CUP, quantificati tra € 26,5 mln ed € 50,6 mln netti nei soli 11 programmi condotti in Italia tra il 2015 e il 2020) ( 9 ) e quelli non economici della ricerca clinica, tra cui l’accesso precoce per i pazienti alle terapie innovative, con conseguente miglioramento degli esiti clinici e della qualità di vita dei pazienti e dei caregiver in generale ( 10 ).…”
Section: Valore Economico Occupazionale E Benefici Per Il Servizio Sa...unclassified